Are habitual runners physically inactive?. Issue 16 (18th August 2018) - Rantalainen, Timo; Pesola, Arto J.; Quittner, Matthew; Ridgers, Nicola D.; Belavy, Daniel L.
ABSTRACT: The World Health Organisation's (WHO) physical activity guidelines recommend 150min/week of moderate- to vigorous-intensity physical activity (MVPA) accumulated in 10 min bouts. To see whether people performing habitual exercise for recreation meet these guidelines, 25 long-distance runners [mean 67 km/wk], 25 joggers [mean 28 km/wk], and 20 sedentary adults wore an ActiGraph GT3X+ accelerometer for 7 days. Sedentary time and bouts were similar in runners and sedentary adults ( p > 0.46). Sedentary adults performed 20 ± 16 min/day of MVPA (usual bout duration (W50%): 9.53 ± 3.45min), with joggers and runners performing 45 ± 31min (W50%: 16.92 ± 9.53min) and 83 ± 58min (W50%: 20.35 ± 8.85min), respectively (p ≤ 0.001 versus sedentary group). Data showed that 65% of the sedentary group, 32% of joggers and 4% of long-distance runners did not meet the WHO guideline for MVPA. Failure to meet the guideline was most prominent in, but not restricted to, runners who reported ≤50km running per week. Self-reported running does not ensure adults meet physical activity guidelines or offset daily sedentary behaviours. On the other hand, the sedentary group was very close in accumulating recommended bouts of MVPA in incidental activities. Future studies should assess whether modification of work and leisure physical activity would be more fruitful than encouraging recreational exercise per se in meeting physical activity guidelines.